2001
DOI: 10.1128/jb.183.24.7318-7328.2001
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptional Response of Bacillus subtilis to Heat Shock

Abstract: In response to heat stress, Bacillus subtilis activates the transcription of well over 100 different genes. Many of these genes are members of a general stress response regulon controlled by the secondary sigma factor, B , while others are under control of the HrcA or CtsR heat shock regulators. We have used DNA microarrays to monitor the global transcriptional response to heat shock. We find strong induction of known B -dependent genes with a characteristic rapid induction followed by a return to near prestim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
242
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 231 publications
(261 citation statements)
references
References 66 publications
17
242
1
1
Order By: Relevance
“…In our analysis, these genes were strongly induced not only under low-temperature growth but also under all the conditions tested. This example also highlights the value of our study, because these genes were previously identified only by Petersohn et al (2001), and would have been missed if the focus had been on the 67 overlapping genes.Around 95 % of genes which were described as being SigBdependent in at least two of the three previous transcriptional profiling studies (Helmann et al, 2001; Petersohn et al, 2001; Price et al, 2001) were validated in the present study (Fig. 6).…”
supporting
confidence: 74%
See 4 more Smart Citations
“…In our analysis, these genes were strongly induced not only under low-temperature growth but also under all the conditions tested. This example also highlights the value of our study, because these genes were previously identified only by Petersohn et al (2001), and would have been missed if the focus had been on the 67 overlapping genes.Around 95 % of genes which were described as being SigBdependent in at least two of the three previous transcriptional profiling studies (Helmann et al, 2001; Petersohn et al, 2001; Price et al, 2001) were validated in the present study (Fig. 6).…”
supporting
confidence: 74%
“…The probes in the custom array targeted a total of 350 genes. The selection of genes was based on: (1) 67 genes that were described to be SigB-dependent in all the three previous transcriptional profiling studies (Helmann et al, 2001; Petersohn et al, 2001; Price et al, 2001), (2) 185 genes that were reported to be SigB-dependent in one or two of the three studies, (3) 52 genes reported in other studies to be probably SigB-dependent (Petersohn et al, 1999b(Petersohn et al, , 2001 Price et al, 2001), (4) 10 additional genes of interest based on unpublished data, and (5) 36 genes that were selected as controls as not exhibiting SigB-dependent expression but encoding a variety of other cellular stress-adaptation reactions (for details see Supplementary Table S1). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations